Tradução e adaptação cultural do banco de itens impacto da dor do PROMIS® para a língua portuguesa - Simon, Kellen Carlos (2014)
Introduction: Pain is a multidimensional subjective phenomenon that involves physical sensory and emotional aspects. Chronic pain has a negative impact on all aspects of life of patients affected, compromising the health-related quality of life (HRQL). In 2004 an assessment of HRQL called Patient-Reported Outcome Measurement Information System (PROMIS®) was conducted from the perspective of the patient. It consists of Item Banks that include physical, psychological and social dimensions. They are statistically calibrated by means of the Item Response Theory (IRT), which enables the researcher to generate individual instruments adapted to the level of commitment of the participant through adaptive testing (CAT). The Item Bank to Measure Pain Interference is a sub-domain of the Physical Health of PROMIS®, to assess the interference of chronic pain on physical, mental and social activities. Objective: To translate and culturally adapt the Item Bank of Pain Interference of PROMIS® into Portuguese and evaluate the semantic, conceptual, cultural and idiomatic equivalence with the original version. Method: The methodology adopted was the FACIT (Functional Assessment of Chronic Illness Therapy), which consists of the process of translation, expert committee review and pre-testing. It is characterized by the use of the decentralized translation model and cognitive interview. Results: Only 6 out of the 41 items showed loss of equivalence (6 semantic and 1 cultural). Despite the low education, understanding was difficult in only two items. Conclusion: The Portuguese version of the Item Bank of Pain Interference of PROMIS® was appropriate to the cultural conditions of the population and kept semantic, idiomatic, and conceptual equivalence with the original version proving to be relevant and being easily understood by the target population.